Racial Disparities in Financial Complaints and the Role of Corporate Social Attitudes - HAYES, RACHEL M.; JIANG, FENG; PAN, YIHUI; TANG, HUAYI (Journal of Accounting Research, 2025)
ABSTRACT Using consumer complaints filed with the Consumer Financial Protection Bureau as a measure for the quality of financial products and services, we present evidence of racial disparities in the service quality received by consumers. Consumers in high‐minority communities file more complaints than those in low‐minority communities, and the racial gap in financial complaints increased by more than 60% during the COVID‐19 pandemic. Using a triple‐difference approach, we establish the role of corporate social attitudes, reflected in, for example, inclusive promotion practices and diversity in leadership, in mitigating the complaint racial gap and its pandemic‐period increase. Our results shed light on how inclusive corporate culture filters through an organization to benefit minority communities and underscore the effect of corporate social attitudes on important stakeholder outcomes.